2020
DOI: 10.3233/atde200163
|View full text |Cite
|
Sign up to set email alerts
|

The Possibilities of Improving Maintenance Through CMMS Data Analysis

Abstract: Maintenance of production equipment is one of the most critical support actions in manufacturing companies for staying competitive. More recently, with the introduction of Industry 4.0, academia, as well as industry, put a lot of effort into condition monitoring in order to implement predictive maintenance. Most stakeholders agree that maintenance need to be more data-driven. However, in order to draw true advantage of data-driven decisions, it is necessary for manufacturing companies to have implemented basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Perceived by employees at the company and to a certain extent analyzed [9], the case company is suffering from recurring failures. To identify these recurring failures, maintenance engineers engage in a manual analysis of work orders within the CMMS.…”
Section: Case Companymentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived by employees at the company and to a certain extent analyzed [9], the case company is suffering from recurring failures. To identify these recurring failures, maintenance engineers engage in a manual analysis of work orders within the CMMS.…”
Section: Case Companymentioning
confidence: 99%
“…Also, it has been reported that reusing experiences as reported by maintenance employees are limited [8]. To improve this situation, companies are advised to analyze their current state and the historical behavior of their equipment [9]. Employing a Computerized Maintenance Management System (CMMS) is essential as a tool in this analytical process [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…By documenting failure reports, disturbances, planned preventive maintenance, etc. in CMMS, the maintenance efficiency and efficacy of the components have been enhanced (Salonen et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%